THE EFFECT OF USING PhET SIMULATION VIRTUAL LAB ON THE UNDERSTANDING OF THE ACID-BASE CONCEPT (A Case Study at Chemistry Education Department, Syiah Kuala University) - Dhea Ulhaq; Latifah Hanum; Habibati Habibati (Chimica Didactica Acta, 2023)
The Covid-19 pandemic has introduced numerous limitations to face-to-face learning, prompting a transition to online platforms. Consequently, this study aims to investigate the impact of using the PhET virtual lab on chemistry education students' understanding of the acid-base concept. Employing a quasi-experimental approach with a one-shot case study design, the research selected two classes (an experimental class and a control class) from the 2021 chemistry education cohort using purposive sampling. Data collection involved the use of tests, as multiple-choice questions, and non-test instruments, including questionnaires. The results of the study indicate that the calculated t-value t count of 14.905 surpassed the critical t-value ttable of 2.262 at a significance level of 5 percent (0.05), leading to the rejection of the null hypothesis (Ho) and the acceptance of the alternative hypothesis (Ha). This finding signifies a significant effect of utilizing the PhET virtual lab on chemistry education students' understanding of the acid-base concept. Moreover, students responded positively to the use of the PhET virtual lab, with 41 percent rating it as good and 40 percent rating it as very good.Keywords: PhET Simulation; Virtual Lab; Distance Learning; e-learning; Acid and Base